Fundamentals of Digital Health Literacy: A Review of the Literature - Junghwan Kim; Bora Jin; Miranda A Livingston; Miriam D Henan; Jihee Hwang (Adult Education Research Conference, 2022)
This study aims to identify the concept of digital health literacy by reviewing contemporary literature. For this purpose, we examine not only a way of understating the concept but also its core competencies by comparing them to those of digital literacy and health literacy.
Keywords: digital health literacy; eHealth literacy; competency; digital literacy; health literacy